Traces of the Archipelago Heritage: Uncovering the Historical Significance of Minangkabau in Negeri Sembilan Culture - Syahriani, Fadilla; Yufriadi, Ferdi; Ngardi, Valensius; Firdaus, Beni (Tarikhuna: Journal of History and History Education, 2024)
This study aims to investigate the deep historical connections between Minangkabau and Negeri Sembilan, two regions with rich cultural heritage in the archipelago. We explore the traces of this heritage to uncover the historical significance of Minangkabau in the formation and development of Negeri Sembilan's culture. The research method involved in-depth historical analyses as well as a careful literature review, which helped us understand the influence that Minangkabau culture has had on the social structure, customary system, values and traditions of the people of Negeri Sembilan. Our results show that this historical footprint reflects not only cultural adoption, but also the complex interaction between Minangkabau and Negeri Sembilan, which has shaped a rich and unique cultural identity in the history of the archipelago. Research findings reveal the deep-rooted nature of this cultural relationship, starting from the early arrival of Minangkabau people in Negeri Sembilan during the 15th and 16th centuries, to diplomatic relations with Raja Mahmud of Pagaruyung in 1773. The historical significance of Minangkabau in Negeri Sembilan culture has important relevance in understanding the cultural dynamics of the region.